(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
In this paper acoustic enclosures with numerous holes presenting complex geometry are investigated using an accelerated two-dimensional boundary element method. The results are obtained using the two-dimensional boundary element method (BEM) accelerated by the adaptive cross-approximation (ACA) and generalized minimum residual (GMRES) solver. A numerical analysis is carried out to assess the accuracy and efficiency of the method compared with the traditional boundary element method.